Linearity measurements of critical Johnson noise thermometer components with low-distortion multitones from a Josephson arbitrary waveform synthesizer. (31st March 2021) - Kraus, M; Drung, D; Krause, C; Palafox, L; Behr, R
Abstract: Quantum-based and low-distortion multitone signals from a Josephson arbitrary waveform synthesizer are used to calibrate critical noise thermometer components between 8 and 240 kHz at increased input noise levels. The example signal path includes a 24-bit ΣΔ analog-to-digital converter (ADC) and a prototype amplifier for Physikalisch-Technische Bundesanstalt's new noise thermometer. The signals consist of odd harmonics of the pattern repetition frequency with growing tone spacing, minimizing the influence of intermodulation distortion during calibration. After a detailed description of the calibration procedure, we compare the multitone spectra with growing tone spacing to ones with equally spaced tones. For the example signal path, gain nonlinearities better than ±2 µV V −1 at input rms noise levels between 9.7 and 465 µV are experimentally demonstrated. Furthermore, we investigate the effect of dither and applied offset voltage on the non-linearity of the ADC.